2018
DOI: 10.4236/ce.2018.96062
|View full text |Cite
|
Sign up to set email alerts
|

Developing Reading Automaticity and Fluency: Revisiting What Reading Teachers Know, Putting Confirmed Research into Current Practice

Abstract: This article revisits research on reading automaticity and fluency with the goal of helping beginning reading teachers put confirmed research findings into current classroom practice. The article examines the concepts of automaticity and fluency, how both impact the development of skillful reading. The article reviews research on: a) reading strategies children use, and b) repeat reading teaching strategies to develop fluency. Case scenarios illustrate key findings. Based on the research and case scenarios, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The research demonstrated that learners made gains in overall language proficiency by EGR, (Hook & Jones, 2004;Ostovar-Namaghi, 2018;Wolf, 2018) proved that EGR increased reading speed and proficiency through increasing the level of automaticity. When students read in their native language, they often read whole 'chunks' of words together, and the more familiar the words are, the faster they read because they automatically recognize what they see, and do not have to process it.…”
Section: Principles Of Extensive Graded Readingmentioning
confidence: 96%
See 1 more Smart Citation
“…The research demonstrated that learners made gains in overall language proficiency by EGR, (Hook & Jones, 2004;Ostovar-Namaghi, 2018;Wolf, 2018) proved that EGR increased reading speed and proficiency through increasing the level of automaticity. When students read in their native language, they often read whole 'chunks' of words together, and the more familiar the words are, the faster they read because they automatically recognize what they see, and do not have to process it.…”
Section: Principles Of Extensive Graded Readingmentioning
confidence: 96%
“…This finding called attention to the benefits of pre-reading activities, as a proficient reading strategy that EFL teachers and learners could adopt to improve their comprehension skills. Anderson (2007), Barrot (2016), andWolf (2018) asserted that prior knowledge of the topic could be the best predictor of comprehension, and its activation could have special importance in generating predictions of the texts' content and promoting EFL readers' comprehension skills.…”
Section: Questionmentioning
confidence: 99%
“…This includes words like sight words and other words that pupils have learnt. Wolf (2018) claimed that automaticity comes through practice and via reading a wide variety of materials. For instance, an avid reader would have encountered sight words such as 'am', 'go', 'has', 'have', 'play' and many more via reading a variety of materials.…”
Section: Reading Fluencymentioning
confidence: 99%
“…Penner-Wilger (2008) highlights that when decoding is an automatic response in reading; there will more attentional resources for text comprehension and also active regulation of one's own reading process. Fluent readers are recognised as those who can decode and comprehend simultaneously while non-fluent readers direct almost all their mental energy or attentional resources to decode and consequently, this leaves very little mental space for effective text comprehension to take place (Kuhn et al, 2010;Wolf, 2018). Therefore, it is fair to say that oral reading fluency should be built in struggling readers especially, so that they can read with accuracy and automaticity and this will subsequently aid them in understanding what they read.…”
Section: Automaticity Theory In the Reading Contextmentioning
confidence: 99%